Can PEP‐3 Provide a Cognitive Profile in Children with ASD? A Comparison Between the Developmental Ages of PEP‐3 and IQ of Leiter‐R. Issue 6 (6th October 2015) - De Giacomo, Andrea; Craig, Francesco; Cristella, Arcangelo; Terenzio, Vanessa; Buttiglione, Maura; Margari, Lucia
Abstract : Background: The assessment of the intelligence quotient (IQ) in children with autism spectrum disorder (ASD) is important to plan a detailed therapeutic‐educative programme. The aim of the study was to evaluate the usefulness of the Psychoeducational Profile‐third edition (PEP‐3) to estimate the general cognitive development of children with ASD. Method: We recruited 30 children with ASD assessed with the Leiter International Performance Scale‐Revised (Leiter‐R) and the PEP‐3. We compared the IQ of the Leiter‐R with the developmental level (DL) of PEP‐3. Results: The findings showed a significant positive correlation between IQ with DL of the cognitive verbal/pre‐verbal ( P  = 0.0005), DL of the area of expressive language ( P  = 0.0004), DL of the area of receptive language ( P  = 0.0001), DL of fine motor ( P  = 0.0066), DL of gross motor ( P  = 0.0217), DL of visuo‐motor imitation ( P  = 0.02), DL of communication ( P  = 0.0001) and DL of motor ( P  = 0.0063). Conclusions: These findings show that the DLs could be considered as indicators of cognitive functioning in ASD.